2012
DOI: 10.3109/10520295.2012.696700
|View full text |Cite
|
Sign up to set email alerts
|

Propidium iodide for making heterochromatin more evident in the C-banding technique

Abstract: The detection of regions of heterochromatin has been the subject of intense investigation. We investigated an adaptation of the commonly used technique by replacing the nonfluorescent dye, Giemsa, by a fluorescent one, propidium iodide. This adaptation produces greater contrast of the heterochromatic bands in metaphase chromosomes and can be especially valuable when the organisms studied possess heterochromatin that is pale and difficult to visualize. We discuss the interactions of these two dyes with DNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 54 publications
(12 reference statements)
0
42
0
Order By: Relevance
“…Metaphasic cells were obtained from the kidney (Bertollo et al 1978;Foresti et al 1993). Heterochromatin was revealed through C banding (Sumner 1972;Lui et al 2012) and nucleolar organizer regions (AgNORs) were revealed through silver nitrate impregnation (Howell and Black 1980). Chromosome types were classified as metacentric (m), submetacentric (sm), subtelocentric (st) or acrocentric (a) based on the arm relationship criteria proposed by Levan et al (1964).…”
Section: Methodsmentioning
confidence: 99%
“…Metaphasic cells were obtained from the kidney (Bertollo et al 1978;Foresti et al 1993). Heterochromatin was revealed through C banding (Sumner 1972;Lui et al 2012) and nucleolar organizer regions (AgNORs) were revealed through silver nitrate impregnation (Howell and Black 1980). Chromosome types were classified as metacentric (m), submetacentric (sm), subtelocentric (st) or acrocentric (a) based on the arm relationship criteria proposed by Levan et al (1964).…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental number (FN) was calculated considering metacentric (m), submetacentric (sm) and subtelocentric (st) chromosomes as having two arms, and acrocentric (a) chromosomes as having only one arm. The heterochromatic pattern was determined by Sumner (1972), with modifications (Lui et al, 2012a) in slides previously analyzed with Giemsa staining (sequential analysis). The Ag-NORs were identified using impregnation by silver nitrate (Howell and Black, 1980), and this preparation was performed on metaphases previously stained by Giemsa and C-banded (sequential analysis).…”
Section: Methodsmentioning
confidence: 99%
“…The heterochromatic distribution pattern was determined according to the protocol described by Sumner (1972), with modifications in the coloring step (Lui et al, 2012). The NORs were identified by AgNOR, described by Howell and Black (1980).…”
Section: Methodsmentioning
confidence: 99%